Pharmacodynamic interaction of fenugreek with insulin and glimepiride in streptozotocin-induced oxidative stress in Sprague Dawley rats (Journal of Advanced Veterinary and Animal Research, 2015)
This study was aimed to assess the effect offenugreek-insulin-glimepiride interaction onoxidative stress in streptozotocin-induced diabeticrats. A total of 56 male Sprague-Dawley rats wererandomly divided into 7 groups (n=8); group 1: servedas Sham, group 2: Diabetic control, groups 3, 4 and 5:served as individual treatment group, groups 6 and 7:treated with combination of insulin-fenugreek andglimepiride-fenugreek, respectively. Serumcreatinine levels of the rats were estimated at 4th and8th weeks during treatment. Thiobarbituric AcidReactive Substances (TBARS), Glutathione (GSH)and protein carbonyls were estimated in the kidneyhomogenate, and relative kidney weights weremeasured at the end of the experiment. Present studyindicated that the levels of TBARS and proteincarbonyls significantly increased in group 2 anddecreased in groups 3 to 7. On the other hand, groups6 and 7 showed significantly lowered valuescompared to the individual treatment groups. Theconcentration of GSH was significantly decreased ingroup 2 and significantly increased in groups 3 to 7,and group 7 showed significantly higherconcentration among all the treated groups. Theserum creatinine concentration in group 2 wassignificantly higher and all treatment groups (3 to 7)showed significantly lowered values at 4th and 8thwks after treatment. The individual treatment groups(3, 4 & 5), antagonised the significant alteration in theantioxidant parameters, and their combination wasrevealed synergism by improving the oxidative statusin diabetic rats. http://dx.doi.org/10.5455/javar.2015.b89